Crystal structure of the antigen‐binding fragment of a monoclonal antibody specific for the multidrug‐resistance‐linked ABC transporter human P‐glycoprotein. Issue 8 (4th August 2016) - Esser, Lothar; Shukla, Suneet; Zhou, Fei; Ambudkar, Suresh V.; Xia, Di
Abstract : The monoclonal antibody UIC2 binds specifically to the extracellular region of the human P‐glycoprotein in a conformationally sensitive manner. The crystal structure of the Fab fragment of UIC2 is reported. Abstract : P‐glycoprotein (P‐gp) is a polyspecific ATP‐dependent transporter linked to multidrug resistance in cancers that plays important roles in the pharmacokinetics of a large number of drugs. The drug‐resistance phenotype of P‐gp can be modulated by the monoclonal antibody UIC2, which specifically recognizes human P‐gp in a conformation‐dependent manner. Here, the purification, sequence determination and high‐resolution structure of the Fab fragment of UIC2 (UIC2/Fab) are reported. Purified UIC2/Fab binds human P‐gp with a 1:1 stoichiometry. Crystals of UIC2/Fab are triclinic (space group P 1), with unit‐cell parameters a = 40.67, b = 44.91, c = 58.09 Å, α = 97.62, β = 99.10, γ = 94.09°, and diffracted X‐rays to 1.6 Å resolution. The structure was determined by molecular replacement and refined to 1.65 Å resolution. The asymmetric unit contains one molecule of UIC2/Fab, which exhibits a positively charged antigen‐binding surface, suggesting that it might recognize an oppositely charged extracellular epitope of P‐gp.